Up and down the little berg: archaeological resource managment in the Natal Drakensberg - Mazel, Aron D (Department of Archaeology, 2016)
The overriding aim of this project was to obtain accurate and detailed information on the rock art and associated Late Stone Age deposits that occur in the rockshelters of the Natal Drakensberg. The emphasis though, was undoubtedly to be rock art. These data were primarily intended for management planning but are also of importance as pure research and permanently stored data. Therefore the project was principally aimed at the following: 1. establishing accurately the localities of as many rock art and other archaeological sites that occur in the Natal Drakensberg. 2. to record fully these sites. The nature of the recording is discussed later. 3. to assess the quantity, quality and general value of the paintings at each site and their condition with regard to natural degradation and vandalism. 4. to gather the basic information essential to devise conservation measures. 5. to make recommendations as to the steps necessary to conserve the paintings. This would include identifying 'bench mark' sites with a view to keeping track of the influence of conservation measures, visitor usage, and natural degradation of the art. 6. the provision of data for future research.